Síntese e caracterização de micropartículas de albumina sérica bovina para emprego em preparo de amostras - Rosa, Mariana Azevedo (2019)
The sample preparation is the step of the analytical procedure that presents higher possibilities of errors and the one that consumes more time. Techniques employing restricted access materials (RAMs) are being developing to minimize the difficult of the complex matrix preparation. The bovine serum albumin (BSA) are being widely used to prepare RAMs, once in association with other materials confers to them the capacity to exclude macromolecules by physics and chemistry mechanisms. In this scenario, we have the main goals of this work: the synthesis of BSA particles (without the use of support material) and their novel use as RAM in solid phase extraction systems to anti-hypertensives determination from untreated human plasma. The microparticles were obtained by the coacervation process, using BSA, phosphate solution 0.2 mmol L-1 (pH=5.00), ethanol, glutaraldehyde 25% and sodium borohydride 1% as synthesis reagents. The characterization studies involved proteins exclusion tests (results above 96% were obtained) and evaluations about kinetic and adsorption isotherms were performed (Elovich and Sips models best fitted the analytes and these studies also shown the ability of the synthetized material to interact both with drugs that have low and high protein binding rate). The material characterization was obtained employing solubility tests, infrared spectroscopy, transmission electron microscopy, atomic force microscopy, zeta potential, dynamic light scattering, porosimetry and thermogravimetric analyses. Two different methods for extraction were developed. One based on the online extraction and another on the solid phase microextraction (SPME). Both evidenced the extraction capacity of the BSA microparticles, and the second one was validated presenting linearity (r ≥ 0.99), precision, accuracy (respecting the limits proposed by the validation guidelines), showed robustness for seven distinct parameters and suitable limits of quantification (ranging from 15 to 100 μg L-1). In addition, the SPME BSA microparticle probes presented favorable characteristics like: resistance, low cost (R$ 0.20/probe), reuse possibility, reproducibility among different (n=3) synthesis (relative standard deviations above 10%), easy handling and portability. Plasma samples from patients whose use the anti-hypertensives were analyzed with SPME LC-MS/MS and quantified concentrations of the drugs were found in the samples.